Tau phosphorylation regulates the interaction between BIN1’s SH3 domain and Tau’s proline-rich domain - Sottejeau, Yoann (Acta Neuropathol Commun, 2015)
INTRODUCTION: The application of high-throughput genomic approaches has revealed 24 novel risk loci for Alzheimer’s disease (AD). We recently reported that the bridging integrator 1 (BIN1) risk gene is linked to Tau pathology. RESULTS: We used glutathione S-transferase pull-down assays and nuclear magnetic resonance (NMR) experiments to demonstrate that BIN1 and Tau proteins interact directly and then map the interaction between BIN1’s SH3 domain and Tau’s proline-rich domain (PRD) . Our NMR data showed that Tau phosphorylation at Thr231 weakens the SH3-PRD interaction. Using primary neurons, we found that BIN1-Tau complexes partly co-localize with the actin cytoskeleton; however, these complexes were not observed with Thr231-phosphorylated Tau species. CONCLUSION: Our results show that (i) BIN1 and Tau bind through an SH3-PRD interaction and (ii) the interaction is downregulated by phosphorylation of Tau Thr231 (and potentially other residues). Our study sheds new light on regulation of the BIN1/Tau interaction and opens up new avenues for exploring its complex’s role in the pathogenesis of AD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40478-015-0237-8) contains supplementary material, which is available to authorized users.